The contribution of vocational training to employment, job-related skills and productivity: evidence from Madeira island - Santiago Budría; Pedro Telhado-Pereira (Institute for the Study of Labor (IZA), 2008)
In this paper, we analyze the transition to the labour market of participants in vocational training in Madeira Island. In a first stage, we investigate how the employment status at different dates (one month, one year, and two years after the completion of the training program) depends on relevant variables, such as age, gender, education and the content and duration of the training. In a second stage, we use the individuals' self-assessment regarding the effectiveness of the training program along three dimensions: employment, job-related skills and productivity. We find that respondents score training activities high in every dimension. Moreover, we find that training is more effective among the educated, indicating that vocational training is far from being remedial. We also find that long training programs and training in the area of tourism are particularly effective.
urn:nbn:de:101:1-20080421194
Keywords: C35; 330; Training; employment; productivity; job-related skills; ordered logit; Berufliche Integration; Berufsbildung; Beschäftigungseffekt; Arbeitsproduktivität; Tourismuswirtschaft; Madeira